Nonocclusive Hepatic Artery Hypoperfusion Syndrome (Splenic Steal Syndrome) in Liver Transplant Recipients - Saad, Wael E. A. (Seminars in Interventional Radiology, 2012)
There are numerous causes of reduced arterial inline flow to the liver transplant despite a patent hepatic artery. These include causes of increased peripheral resistance in the hepatic arterial bed, siphoning of the hepatic arterial flow by a dominant splenic artery (splenic steal syndrome), functional reduction of hepatic arterial flow in response to hyperdynamic portal inline flow, and small hepatic graft relative to normal portal inline flow (relative increase of portal flow). These causes are incompletely understood, and perhaps the most controversial of all is the splenic steal syndrome, which is possibly an underrecognized cause of graft ischemia in the United States. Splenic steal syndrome presents nonspecifically as graft dysfunction; if overlooked, it may lead to graft failure. Its incidence is reported to be 0.6 to 10.1% in liver transplant recipients, with some institutions performing prophylactic and/or posttransplant treatment procedures in up to a quarter of their transplant recipients. This wide disparity in the incidence of the diagnosis is probably because there are no objective diagnostic imaging criteria. This article presents a review of the literature that addresses the differential diagnostic considerations of hepatic artery hypoperfusion (splenic steal syndrome included) in the absence of an anatomical defect (hepatic artery stenosis, thrombosis, and/or kinks).
Keywords: transplant; liver; vascular complications; splenic steal; hypoperfusion; buffer response